Variability and plus tree selection in Swietenia macrophylla from Kerala, South India - Aleena Thomas Moor1 , A.V. Santhoshkumar1*, T. K. Hrideek2 , E.V. Anoop1 and Manju Elizabeth1 (Electronic Journal of Plant Breeding, 2021)
Big leaf mahogany (Swietenia macrophylla, King) is a valuable Neotropic timber species. It is the first extensively traded timber species to be listed in Appendix II of the CITES in 2002. The tree was introduced to India in 1795 and Kerala in 1872. The present study aimed at selecting plus trees of Swietenia macrophylla and evaluating their genetic variability. Forty-five plus trees were selected from 593 candidate trees spread over fifteen locations in Kerala based on baseline regression of trunk volume to crown volume, followed by scoring for qualitative characters. The clean bole height, GBH, crown width, crown volume and wood density of CPTs ranged from 6 to 13.4 m, 0.75 to 2.00 m, 8 to 15 m, 7 to 16 m and 21 to 23 mm, respectively. The plus trees were grouped into five clusters based on their quantitative and qualitative characters. Clustering was independent of the geographical location indicating a lack of development of any land races in the species.